ANALYSIS OF ARTICLE 13 OF BOGOR DISTRICT REGIONAL REGULATION NUMBER 5 OF 2015 CONCERNING PROTECTION OF WOMEN AND CHILDREN FROM ACTS OF VIOLENCE - Azhari, Marisa; Nuraeny, Henny (Fakultas Hukum Universitas Djuanda, 2024)
Violence against women and children is a serious problem that affects the quality of life of victims and threatens their human rights. This article will focus on analyzing the implementation of Article 13 letter b. This research uses a qualitative approach with descriptive-analytical methods. Data collection was carried out through document studies in the form of Analysis of Regional Regulations and related publications. The second data collection was through observation, namely confirmation from victims of harassment at SMPN 1 Cigombong. This research found that the implementation of this Regulation, especially Article 13 concerning victims' rights, is still not running optimally. The main findings show that there are still many cases of violence against women and children in Bogor Regency who have not received adequate health and psychological recovery. For example, the case at SMPN 1 Cigombong, where a teacher committed an act of sexual violence against a female student, shows that despite recovery efforts, services are not sustainable, and the trauma experienced by the victim is not handled properly.